2002
DOI: 10.18553/jmcp.2002.8.6.459
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Single-Patient Drug Trial Methodology for Personalized Management of Gastroesophageal Reflux Disease

Abstract: Omeprazole was the appropriate treatment in only 52% of these chronic users of acid-suppressing drugs. Eleven of 27 trials (41%) indicated that ranitidine was the preferred treatment. The SPT method proved acceptable to patients, feasible to administer, and reproducible. It can statistically discriminate effectiveness and adverse events and serve as a useful, prognostic tool in community practice by determining the least costly, evidence-based, appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Of course, the pilot nature of this study and the sample size involved means that a full exploration of views is unlikely to have been achieved but the findings support and complement other similar research, which has found patient response to be very positive and established evidence of consumer demand for n-of-1 trials outside the UK[5,6,8,9,12]. Nickles et al recently published the results of a qualitative study conducted in Australia, where n-of-1 trials are more widely recognised and established[7].…”
Section: Discussionmentioning
confidence: 53%
“…Of course, the pilot nature of this study and the sample size involved means that a full exploration of views is unlikely to have been achieved but the findings support and complement other similar research, which has found patient response to be very positive and established evidence of consumer demand for n-of-1 trials outside the UK[5,6,8,9,12]. Nickles et al recently published the results of a qualitative study conducted in Australia, where n-of-1 trials are more widely recognised and established[7].…”
Section: Discussionmentioning
confidence: 53%
“…A remarkable 40% of patients with gastroesophageal reflux disease (GERD) treated with proton pump inhibitors (PPIs) were found by the single-patient trial (SPT) method to achieve the same or better outcomes as these patients treated with ranitidine. 7 This work by Wolfe, del Rio, Weiss, et al suggests that spending on drug treatment for GERD could be reduced by more than one third since histamine-2 receptor antagonists such as ranitidine cost managed care organizations (MCOs) $.50 or less per day of therapy versus $4 or more per day of therapy with a PPI. All of the H2-antagonists (cimetidine, ranitidine, famotidine, and nizatidine) were available from generic manufacturers by mid-2002.…”
Section: ■■ Single-patient Trial (Spt) Method-substitute For Expert Omentioning
confidence: 99%
“…Patients with GERD usually require a continue therapy, either continuous, at demand, or intermittent [20]. Additionally, GERD has heterogeneous recurrent clinical expressions and many patients frequently experience symptomatic setbacks, which could be easily self-evaluated [21][22][23].…”
Section: Introductionmentioning
confidence: 99%